2022
DOI: 10.3389/fnagi.2021.761932
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Functioning in a Community-Based Volunteer Population: Differences Between Participant- and Study Partner-Report

Abstract: Introduction: Impaired awareness in dementia caused by Alzheimer’s disease and related disorders made study partner-report the preferred method of measuring interference in “instrumental activities of daily living” (IADL). However, with a shifting focus toward earlier disease stages and prevention, the question arises whether self-report might be equally or even more appropriate. The aim of this study was to investigate how participant- and study partner-report IADL perform in a community-based volunteer popul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Conversely, the finding of participant underreport might reflect a decrease in awareness. Our findings add to a growing body of literature indicating that participants and study partners report differently on the participants' cognitive and functional performance, even when participants are cognitively normal (14,(26)(27)(28)(29). As both self-reported and study partner-reported IADL functioning has been related to objective cognitive performance and future cognitive decline (15,17), including both assessments in early disease stages may have added value and be beneficial for identifying those at risk for disease progression.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Conversely, the finding of participant underreport might reflect a decrease in awareness. Our findings add to a growing body of literature indicating that participants and study partners report differently on the participants' cognitive and functional performance, even when participants are cognitively normal (14,(26)(27)(28)(29). As both self-reported and study partner-reported IADL functioning has been related to objective cognitive performance and future cognitive decline (15,17), including both assessments in early disease stages may have added value and be beneficial for identifying those at risk for disease progression.…”
Section: Discussionsupporting
confidence: 53%
“…Slightly more than half the dyads were in concordance, while approximately a quarter of participants self-reported more difficulty and approximately a fifth of participants self-reported less difficulty than their study partners. Another study previously found a similar proportion of cognitively normal participants who reported more difficulties than their study partners (14).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…One of these characteristics is the confirmation of cognitive decline by an observer: when an observer, such as a partner, relative, or friend, corroborates the experience of impairments in cognitive functioning, this may be considered an objective confirmation of the individual's self‐perceived impairment in cognitive functioning. A discrepancy between self and study partner report has been found in multiple studies 12–15 . In an analysis of various items probing self‐perceived cognitive functioning, Amariglio et al 16 .…”
Section: Introductionmentioning
confidence: 99%